Algebra 1

Published by Prentice Hall
ISBN 10: 0133500403
ISBN 13: 978-0-13350-040-0

Chapter 1 - Foundations for Algebra - 1-2 Order of Operations and Evaluating Expressions - Practice and Problem-Solving Exercises: 53

Answer

Yes

Work Step by Step

We can do $(1+5)^{2}-\frac{18}{3}=(6)^{2}-\frac{18}{3}=36-\frac{18}{3}=36-6=30$ or we can do $(1+5)^{2}-\frac{18}{3}=(1+5)^{2}-6=6^{2}-6=36-6=30$. These both give the same solution.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.